Factors Affecting Financial Management Behavior of Millennial Generation: The Role of Financial Attitude, Financial Literacy, Locus of Control, and Financial Knowledge - Zaen, Mudrikah; Innayah, Maulida Nurul; Purwidianti, Wida; Aryoko, Yudhistira Pradhipta (Universitas Pamulang, 2024)
This study aims to determine the effect of financial attitude, financial literacy, locus of control, and financial knowledge on financial management behavior. The population in this study is the millennial generation in Central Java. The type of research used in this study is descriptive-quantitative with a data processing technique using SEM (Structural Equation Modeling) based on partial least squares (PLS), which includes an outer model and an inner model. The sampling technique used the Slovin formula, which resulted in 135 respondents. The results showed that financial attitude, financial literacy, and locus of control have a positive and significant influence on financial management behavior. However, financial knowledge does not influence financial management behavior.